Strong, Machinable Carbon Aerogels for High Performance Supercapacitors - Kim, Christine H. J.; Zhao, Dandan; Lee, Gyeonghee; Liu, Jie (Advanced functional materials, 2016)
Designing macroscopic, 3D porous conductive materials with high mechanical strength is of great importance in many fields, including energy storage, catalysis, etc. This study reports a novel approach to fabricate polyaniline‐coated 3D carbon x‐aerogels, a special type of aerogels with mechanically strong, highly cross‐linked structure that allows the originally brittle aerogels machinable. This approach is accomplished by introducing a small amount of graphene into the sol–gel process of resorcinol and formaldehyde, followed by physical activation and subsequent cross‐linking with polyaniline via electropolymerization. The resulting x‐aerogels are not only porous and conductive, but also mechanically robust with high compressibility and fast recovery. The strong combination of these properties makes the x‐aerogels promising for high performance supercapacitors that are designed to provide additional functionality for wearable and portable electronics. Such multi‐functionality leads to a significant increase in electrochemical performance, in particular high volumetric capacitance, which results from the more densely packed electroactive structure in three dimensions. More importantly, monoliths of carbon x‐aerogels are machinable into thin slices without losing their properties, thus enabling effective integration into devices with different sizes and shapes. Strong, machinable carbon aerogels are reported, developed to be not only porous and conductive, but also mechanically robust with high compressibility and fast recovery. The synergistic combination of these properties makes the aerogels promising for high performance supercapacitors that are designed to provide additional functionality for wearable and portable electronics.